Where the Global Market Is - Natalia Conroy (Journal of Economic Sociology, 2015)
Koray Çalişkan is among those few scholars (such as D. MacKenzie, A. Preda, D. Muniesa), to have recently conducted pioneering work in the field of social studies of finance (SSF). In his highly innovative book “Market Threads”, the author presents an impressive example of how it is possible to study a global market by using micro-methods and, particularly multi-sited ethnography, which anthropologist George Marcus described in the mid-1990s as a tool for understanding phenomena that we couldn’t fully grasp in just one place [Marcus 1995]. Çalişkan chose the cotton market for his study and ‘followed’ cotton through seven ‘sites’ across Turkey, Egypt and the USA. He argues that in market studies a researcher’s main goal is to show how prices are realized, and he introduces a view of the global cotton market as a multiplicity of regional market platforms relying heavily on ‘human bridges’ (or, networks). Agents at each end of these ‘bridges’ routinely generate indicative prices: these are ‘prosthetic devices’ designed to help agents ‘on the ground’ and set actual prices. Çalişkan lets us see this price realization on different levels and writes an exciting ethnographic story woven from the real voices of international merchants, regional traders and local farmers. Additionally, his book provides informative reading for anyone interested in the history of neoliberal reform in the Middle East. Unfortunately though, as with any first attempt to deploy a new and ‘muddy’ methodological tool, the study hardly answers the question of how multi-sited ethnography itself was conducted.